Scott Drawer Interview (UK Sport): Solving problems (2013)
Dr. Scott Drawer is Deputy Director of Performance Solutions at English Institute of Sport (EIS). Scott and his team have been credited with making a major contribution to the success of UK athletes at the London Olympics. Responsible for a budget of over £10 million, the UK Sport website describes his role as being, `the conductor of scientific, medical and technological expertise to support the best British athletes….`. This appears to be a remarkably wide ranging job, and one that sounds highly complex and challenging. The author of this interview thought that it would be useful to hear a little more on what the job actually entailed, and how it is carried out. He asked Scott to describe the key elements of his work.